2005
DOI: 10.1532/hsf98.20041042
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Radial Artery and Hand Circulation by Computed Tomography Angiography: A Pilot Study

Abstract: CTA is useful and safe for detection of radial artery calcific disease and assessment of the forehand circulation and its anatomic variations. Preoperative imaging of the RA is a means to avoid unnecessary forearm exploration or inadvertent use of a diseased conduit in coronary artery bypass candidates with multiple risk factors such as diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…But, diffuse calcified radial artery in case with coronary artery disease have been reported by Dogan et al using computed tomography of the forearm before the radial artery harvesting in CABG patients for the first time [7]. In our study, because of this method is cheapest and easy to use and simple we used forearm X-ray films for evaluation of radial artery calcific disease in largest patient who diagnosed ESRDP and high incidence of peripheral artery calcification was recorded in this groups.…”
mentioning
confidence: 67%
“…But, diffuse calcified radial artery in case with coronary artery disease have been reported by Dogan et al using computed tomography of the forearm before the radial artery harvesting in CABG patients for the first time [7]. In our study, because of this method is cheapest and easy to use and simple we used forearm X-ray films for evaluation of radial artery calcific disease in largest patient who diagnosed ESRDP and high incidence of peripheral artery calcification was recorded in this groups.…”
mentioning
confidence: 67%
“…Other investigators have reported the use of pulse oximetry pre‐ and intraoperatively, coupled with the Allen test . Regardless of the technique used, in 10‐20% of cases, there is either a morphologic or circulatory contraindication to the use of the RA . Finally, surgeons should know whether the RA that is to be harvested has been recently cannulated during a diagnostic cardiac catheterization.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of calcifications of the radial artery, harvesting a radial forearm flap should be reconsidered. Other imaging modalities, like DSA, computed tomographic angiography 6 , magnetic resonance with a contrast agent 18 and perfusion examinations 9 , should be reserved for exceptional cases when Allen's test and duplex ultrasound show pathological results and other flaps are not available. …”
Section: Discussionmentioning
confidence: 99%